FIKIH TASAMUH: MERAJUT HARMONI DALAM KERAGAMAN PENDAPAT - A.P. Kau, Sofyan; Suleman, Zulkarnain (Al-Mizan, 2015)
Interpretation and understanding of the authoritative sources of Islam (Quran and Hadith) are not single, but diverse. Therefore, the diversity and differences understanding are inevitable and historical. In the midst of diversity and difference are needed openness, respect and it donât negate the different opinions, and distanced himself from the claim of truth single opinion is a moral imperative to harmony. This paper offers five principles for knitting harmony intended, namely: mandatory precedence (Wajib) over the Sunnah; promoting scientific paradigm on religious, agreed on the principle (qathi-usul) and tolerant on the particulate matter (zhanni-furu), emphasizes the relationship to the debate; and did not highlight his own opinion as he cornered a different opinion. These five principles of fiqh tasamuh (jurisprudence of tolerant).